2020
DOI: 10.31083/j.jin.2020.03.172
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-like mechanism of honokiol in a rodent model of corticosterone-induced depression

et al.

Abstract: Depression is closely linked to hypothalamus-pituitaryadrenal axis hyperactivity. Honokiol, a biphenolic lignan compound obtained from the traditional Chinese medicine Magnolia officinalis, can reduce the activity of the hypothalamus-pituitary-adrenal axis and improve depression-like behavior caused by hypothalamuspituitary-adrenal axis hyperactivity. The current study investigated the specific mechanism of action of this effect. A depression model was established by repeated injections of corticosterone to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Its pharmacological effects include antiinflammatory, antithrombotic, antiarrhythmic, antioxidative, central depressant, muscle relaxant, and anxiolytic effects [82]. In the endocrine system, honokiol activates the ERK/cfos signaling pathway, increases levels [83], increases the mRNA expression of glucocorticoid receptors in the hippocampus [84], improves insulin resistance in type 2 diabetic db/db mice [85], and inhibits 5-alpha-reductase type 1, modulating testosterone levels in vitro [82]. Nevertheless, its effects on the thyroid gland have never been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Its pharmacological effects include antiinflammatory, antithrombotic, antiarrhythmic, antioxidative, central depressant, muscle relaxant, and anxiolytic effects [82]. In the endocrine system, honokiol activates the ERK/cfos signaling pathway, increases levels [83], increases the mRNA expression of glucocorticoid receptors in the hippocampus [84], improves insulin resistance in type 2 diabetic db/db mice [85], and inhibits 5-alpha-reductase type 1, modulating testosterone levels in vitro [82]. Nevertheless, its effects on the thyroid gland have never been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of depression was previously reported to be associated with synaptic plasticity disorders ( Pilar-Cuéllar et al, 2013 ; Li et al, 2020b ). Our previous studies have shown that honokiol exhibits significant antidepressant-like effects by affecting tryptophan metabolism and reducing the serum levels of corticosterone to improve neuronal plasticity ( Zhang et al, 2019 ; Zhang et al, 2020 ). Furthermore, honokiol was shown to bind to neural cell adhesion molecules to enhance neuronal survival and synaptic plasticity ( Xu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The medicinal Magnolia bark in the 'Chinese Pharmacopoeia' is commonly used to treat dampness injury, phlegm cough and other symptoms [1] . Lignans (including magnolol and honokiol), the main active components of M. officinalis, have many potential pharmacological effects, such as antitumor, antiviral, antibacterial, antiinflammatory, antioxidative, liver function-protective, and cardiovascular disease effects (Liao et al 2015;Pan et al 2024;Shen et al 2017;Xian et al 2015;Zhang et al 2020). Bioinformatics has previously investigated and discovered certain genes associated with the MVA pathway or the Dirigent gene family of M. officinalis, providing a theoretical basis for the molecular mechanism of M. officinalis biosynthesis (Zha et al 2015;Zhang et al 2024).…”
Section: Introductionmentioning
confidence: 99%